Diagnosis and treatment planning in dentistry - Treatment planning in dentistry; Stefanac, Stephen J.; Nesbit, Samuel Paul (St. Louis, Missouri : Elsevier, 2024)
'A full-color, all-in-one reference, Diagnosis and Treatment Planning in Dentistry, 4th Edition helps you create person-centered dental treatment plans for adolescent and adult patients. Using evidence-based research, this text shows how risk assessment, prognosis, and expected treatment outcomes factor into the planning process. Detailed coverage guides you through each phase of the treatment plan. New to this edition are chapters covering digital tools used in treatment planning and revised content in all chapters. The book renews a core section that describes how to plan and provide optimal oral health care for unique patient populations'--
Patient evaluation and assessment -- Common diagnoses in dentistry -- Evidence-based treatment planning: assessment of risk, prognosis, and expected outcomes -- Digital tools for diagnosis and treatment planning -- Developing the treatment plan -- Interprofessional treatment planning -- Ethical and legal considerations when treatment planning -- The systemic phase of treatment -- The acute phase of treatment -- The disease control phase of treatment -- The definitive phase of treatment -- The maintenance phase of care -- Patients with special needs -- Patients who are substance dependent -- Patients with anxiety, fear, or a phobia of dental care -- Patients with a psychological disorder -- Adolescent patients -- Geriatric patients -- Patients who are motivationally or financially challenged.
Includes bibliographical references.
Description based on online resource; title from electronic title page (ClinicalKey, viewed May 12, 2023).
Log in https://ebooks.health.elsevier.com/login Username: pdalukmkl@gmail.com Password: KualaLumpur12345#
Keywords: Comprehensive Dental Care -- methods; Patient Care Planning; Planning Techniques